2012
DOI: 10.1021/ic201971t
|View full text |Cite
|
Sign up to set email alerts
|

Isostructural Dinuclear Phenoxo-/Acetato-Bridged Manganese(II), Cobalt(II), and Zinc(II) Complexes with Labile Sites: Kinetics of Transesterification of 2-Hydroxypropyl-p-nitrophenylphosphate

Abstract: Using the dinucleating phenol-based ligand 2,6-bis[3-(pyridin-2-yl)pyrazol-1-ylmethyl]-4-methylphenol] (HL(2)), in its deprotonated form, the six new dinuclear complexes [M(II)(2)(L(2))(μ-O(2)CMe)(2)(MeCN)(2)][PF(6)] (M = Mn (2a), Co (3a), Zn (4a)) and [M(II)(2)(L(2))(μ-O(2)CMe)(2)(MeCN)(2)][BPh(4)] (M = Mn (2b), Co (3b), Zn (4b)) have been synthesized. Crystallographic analyses on 2b·2MeCN, 3b·2MeCN, and 4b·2MeCN reveal that these complexes have closely similar μ-phenoxo bis(μ-carboxylato) structures. The phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 111 publications
7
46
0
Order By: Relevance
“…The coordination patterns and binding models of the catalystsubstrate complex have been largely explored in literature [15,16,20,30,42] and after rigorous considerations two plausible catalytic cycles having reasonably good agreement with our kinetic results have been postulated from the previous representative mechanisms. The substrate molecule binds as a dianionic mononitrophenyl phosphate to the complex having phosphatase activity.…”
Section: Mechanistic Implicationssupporting
confidence: 63%
See 1 more Smart Citation
“…The coordination patterns and binding models of the catalystsubstrate complex have been largely explored in literature [15,16,20,30,42] and after rigorous considerations two plausible catalytic cycles having reasonably good agreement with our kinetic results have been postulated from the previous representative mechanisms. The substrate molecule binds as a dianionic mononitrophenyl phosphate to the complex having phosphatase activity.…”
Section: Mechanistic Implicationssupporting
confidence: 63%
“…Over the years, synthetic Zn(II) (and also other transition metal) complexes have been judiciously studied as phosphate ester models taking into account their extraordinary Lewis acidity, redox rigidity, nucleophile generation, leaving group stabilization and physiological relevancy [11,12]. However, among the numerous catalytically promiscuous Zn(II) derivatives [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] some complexes show low activity, others require rigorous synthetic conditions or have high toxicity. Therefore the development of new efficient metallocatalysts is still a tough challenge in the field of biocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Since Sargeson's early work other examples of functional or spectroscopic model complexes for several dicobalt(III)/(II) complexes have been reported. 149,[176][177][178][179][180][181][182][183][184][185] For the Co(II) complexes in the present studies the activity towards organophosphoesters using BDNPP, was investigated (Table 2). 136 All complexes are good functional mimics for phosphodiesterases and show one pK a relevant for hydrolysis.…”
Section: Mechanism Of Phosphodiester Hydrolysis For the Co(ii) Complexesmentioning
confidence: 99%
“…12 In addition, it was shown that the monomeric [α-PW 11 O 39 Zr-(µ-OH)(H 2 O)] 4− (ZrK 1 : 1) species is present in aqueous solution at near-neutral pD and that this species is responsible for the hydrolysis of the phosphoester bond in BNPP. 19 As a previous study showed that the solution speciation of this POM is highly dependent on several factors such as pD, temperature, initial concentration, ionic strength and substrate concentration, 12 the speciation behavior of ZrK 2 : 2 at the conditions used to study HPNP hydrolysis was studied in detail. Theoretical studies have shown that when ZrK 1 : 1 interacts with NPP or BNPP, it prefers to form monodentate complexes which are more stable than the corresponding bidentate complexes.…”
Section: Introductionmentioning
confidence: 99%
“…reaction show that cyclic phosphate (CycP), with a 31 P resonance at 18 ppm, is formed 19,28. At the end of hydrolysis, no HPNP resonances were detected in both 1 H and 31 P NMR spectra, indicating full conversion of HPNP into cyclic phosphate and NP.Several control experiments were performed.…”
mentioning
confidence: 99%